Effects of fruits and vegetables on gut microbiota in a mouse model of metabolic syndrome induced by high‐fat diet. Issue 2 (5th November 2022) - Yu, Congcong; Guo, Cang; Geng, Xueying; Yao, Yuyang; Guo, Junxia; Zhang, Yanzhen; Zhang, Jing; Mi, Shengquan
Abstract: The aim of this study was to evaluate the effect of fruit and vegetable intake on gut microbiota using a mouse model of metabolic syndrome (MS) induced by a high‐fat diet. Forty‐eight male mice were randomly divided into four groups, control group (C), high‐fat diet‐fed model group (H), high fat plus low intake of fruits and vegetables diet‐fed group (H.LFV), high fat plus high intake of fruits and vegetables diet‐fed group (H.HFV), and each group were fed for 60 days. During the experiment, mouse body weights were recorded and fecal samples were collected. Cetyltrimethyl ammonium bromide (CTAB) method was used to extract fecal bacterial DNA, and the purity and concentration of the DNA were detected by electrophoresis. DNA samples underwent PCR amplification (primers in 16 S V4 (515F and 806R)). Raw sequencing data were processed, and sample complexity and multiple‐sample comparisons were investigated. Mouse organ coefficient, serum lipid levels, fecal TC (total cholesterol) and TBA (total bile acid) levels, and hepatic glutathione and malondialdehyde levels were determined. Compared to the H group, the fecal TC and TBA levels decreased significantly in the H.HFV group ( p < .05), and hepatic glutathione and malondialdehyde levels decreased significantly in both H.LFV and H.HFV groups ( p < .05). Decreased abundance of Firmicutes, Burkholderiales, Syntrophomonas, and Pseudomonadales in gut microbiota was observed in H.LFV and H.HFV groups compared to the H group. The Anosim results showed significant differences in pairwise comparison between groups. The linear discriminant analysis effect size (LEfSe) results showed that k_bacteria not only exhibited statistically differences between H and C groups but also among H.LFV, H.LFV, and H groups, and hence, could be used as a biomarker between groups. To sum up, fruit and vegetable powder could increase the fecal excretion of TC and TBA, and the antioxidant capacity in C57BL/6N mice. Meanwhile, the mechanism that fruit and vegetable powder could prevent MS in C57BL/6N mice was related to the decreased abundance of gut microbiota, including Firmicutes, Syntrophomonadales, and Pseudomonadales. Hence, fruit and vegetable powder could be used as a recommended food to regulate gut microbiota and prevent the occurrence of MS‐related diseases. Abstract : The aim of this study was to evaluate the effect of fruit and vegetable intake on gut microbiota using a mouse model of metabolic syndrome (MS) induced by high‐fat diet. our research shows that continuous intake of a certain amount of fruits and vegetables can significantly inhibit the increase of physical fitness, normalize the liver lipid accumulation in mice with metabolic syndrome, and reduce the risk of metabolic diseases; increase C57BL/ TC and TBA excretion levels in feces of 6N mice; improvement of liver antioxidant levels in C57BL/6N mice. In addition, fruit and vegetable intake not only promoted the abundance of Firmicutes, but also inhibited Bacteroidetes, thereby increasing the diversity of gut microbiota in mice. Therefore, fruits and vegetables have a good prebiotic effect in the regulation of intestinal flora, and have the potential to prevent and improve metabolic syndrome and other related diseases.